THE ASSOCIATION BETWEEN VITAMIN D DEFICIENCY, INFLAMMATORY FACTORS, AND RESPIRATORY DISTRESS AMONG NEONATES: RETROSPECTIVE COHORT STUDY - Doroodgar Moein; Aminian Alireza; Doroodgar Masoud; Abolhassan Choobdar Farhad; Yousefi Zoshk Mojtaba; Kowsari Kourosh; Kazemi Galougahi Mohammad Hassan (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background and Aim: Neonatal respiratory distress is a common complication among new-borns with fatal consequences if left untreated. Inflammation plays an important role in the pathophysiology of this condition as the neonate’s immune system is not fully developed upon birth. Previously, it has been reported that vitamin D levels are attributed to inflammatory responses in adults and animal models. Hence, we aimed at evaluating the association between the vitamin D deficiency and inflammatory markers among neonates who suffer from respiratory distress after birth.